What effect does an animal robot called CuDDler have on the emotional response of older people with dementia? A pilot feasibility study - Moyle, W.; Jones, C.; Sung, Billy; Bramble, M.; O'Dwyer, S.; Blumenstein, M.; Estivill-Castro, V. (2016)
The development of companion animal robots is of growing interest. These robots have recently been marketed to older adults with dementia as a means of encouraging social engagement and reducing behavioural and psychological symptoms of dementia. This paper outlines the results of a pilot study that sought to assess the feasibility and effect of using a robotic companion animal called CuDDler on engagement and emotional states of five older adults with dementia living in nursing home care. CuDDler is a prototype robot developed in Singapore. Despite their cognitive decline, the study participants raised a number of concerns regarding the feasibility and tolerability of CuDDler. The effectiveness of CuDDler was also limited in these participants, although one participant with visual agnosia benefited greatly from the one-on-one experience. The findings demonstrate the importance of companion robots being developed that are of an appropriate size, weight and shape for older people, including those with dementia, and a realistic animal shape that does not encourage thoughts of it being a toy. Our conclusions indicate the need for further studies on the development and use of companion robots, and investigation of the comparative benefits of social robots both compared to and in association with human interactions.